Antibiotic dispensing behaviors for pediatric diarrhea: A qualitative study of informal healthcare providers in rural Bangladesh - Debashish Biswas; Melissa H. Watt; Aparna Mangadu; Jyoti Bhushan Das; Mohammad Saeed Munim; Ridwan Mostofa Shihab; Zahid Hasan Khan; Mohammad Ashraful Amin; Ishtiakul Islam Khan; Md. Taufiqul Islam; Olivia R. Hanson; Eric J. Nelson; et al. (PLoS ONE, 2025)
Antibiotic resistance is a significant public health concern and requires coordinated efforts to promote antibiotic stewardship. In rural Bangladesh, informal healthcare providers known as “village doctors” are a primary source of antibiotics for a range of ailments, including pediatric diarrhea. This qualitative study explored the factors influencing antibiotic dispensing practices for pediatric diarrhea among village doctors in the Chattogram district of Bangladesh. In May 2023, we conducted in-depth interviews with 18 village doctors and analyzed the data using thematic analysis approach. The resulting themes were mapped onto the five domains of the Social Ecological Framework (SEF) to identify the multi-level drivers of antibiotic dispensing practices. At the individual level, antibiotic provision for treatment of pediatric diarrhea is influenced by village doctors’ clinical knowledge, training, and beliefs about antibiotics. At the interpersonal level, village doctors often alter their antibiotic dispensing practices based on patient and caregiver demands and influences from pharmaceutical companies. Organizational level factors include financial incentives from medication sales and pharmaceutical companies, resource constraints, diagnostic limitations, and a competitive healthcare landscape. We also identified that cultural expectations for rapid recovery through antibiotics and widespread community access to antibiotics at the community level. Finally, at the policy level, we identified weak regulatory frameworks, inadequate enforcement mechanisms, and healthcare system challenges that position village doctors as essential but unregulated providers. The findings highlight the multi-level drivers for inappropriate antibiotic use. Effective interventions should enhance clinical training, address economic incentives, promote community education, and establish clear regulatory frameworks. Future strategies should consider the interconnected nature of these influences rather than targeting isolated levels.